Changes in the treatment of Enterococcus faecalis infective endocarditis in Spain in the last 15 years: from ampicillin plus gentamicin to ampicillin plus ceftriaxone. (11th August 2014) - Pericas, J. M.; Cervera, C.; del Rio, A.; Moreno, A.; Garcia de la Maria, C.; Almela, M.; Falces, C.; Ninot, S.; Castañeda, X.; Armero, Y.; Soy, D.; Gatell, J. M.; et al.
Abstract The aim of this study was to assess changes in antibiotic resistance, epidemiology and outcome among patients with Enterococcus faecalis infective endocarditis (EFIE) and to compare the efficacy and safety of the combination of ampicillin and gentamicin (A+G) with that of ampicillin plus ceftriaxone (A+C). The study was a retrospective analysis of a prospective cohort of EFIE patients treated in our centre from 1997 to 2011. Thirty patients were initially treated with A+G (ampicillin 2 g/4 h and gentamicin 3 mg/kg/day) and 39 with A+C (ampicillin 2 g/4 h and ceftriaxone 2 g/12 h) for 4–6 weeks. Increased rates of high‐level aminoglycoside resistance (HLAR; gentamicin MIC ≥512 mg/L, streptomycin MIC ≥1024 mg/L or both) were observed in recent years (24% in 1997–2006 and 49% in 2007–2011; p 0.03). The use of A+C increased over time: 1997–2001, 4/18 (22%); 2002–2006, 5/16 (31%); 2007–2011, 30/35 (86%) (p <0.001). Renal failure developed in 65% of the A+G group and in 34% of the A+C group (p 0.014). Thirteen patients (43%) in the A+G group had to discontinue treatment, whereas only one patient (3%) treated with A+C had to discontinue treatment (p <0.001). Only development of heart failure and previous chronic renal failure were independently associated with 1‐year mortality, while the individual antibiotic regimen (A+C vs. A+G) did not affect outcome (OR, 0.7; 95% CI, 0.2–2.2; p 0.549). Our study shows that the prevalence of HLAR EFIE has increased significantly in recent years and that alternative treatment with A+C is safer than A+G, with similar clinical outcomes, although the sample size is too small to draw firm conclusions. Randomized controlled studies are needed to confirm these results.